Prophetic Parenting dan Kesejahteraan Psikologis Pada Mahasiswa - Lusi M. Rahmayani; Sumedi P. Nugraha (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2015)
The purpose of this study was to examine the relationship between prophetic parenting and psychological well-being. There were 102 students participated in this study. Two scales, psychological well-being and prophetic parenting were used in this study. The psychological well-being scale was compiled by Jordan (2011) and is based on six aspects of psychological well-being ofRyffand Keyes (1995). The prophetic parenting scale was compiled by researchers were based on six aspects of parenting prophetic from Suwaid (2010). The results showed that there was a positive relationship between parenting prophetic father and psychological well-being of students (r = 0.448; p < 0.05), and there is also a positive relationship between parenting prophetic mother and psychological well-being of students (r = 0.310; p < 0.05). Keywords: psychological well-being, prophetic parenting, undergraduate students